Synergistic Effect of Phosphorus, Magnesium, and Copper on Phenolic and Flavonoid Production in Paddy Rice - Tri Candra Setiawati; Vega Kintaghea Rewisa; Desi Febiola; Laily Mutmainah; Ali Wafa; Syahrul Efendi; Lolita Endang Susilowati (Postgraduate, University of Mataram, 2025)
Secondary metabolites are crucial for plant resistance to biotic and abiotic stress. Fertilization with phosphorus (P), magnesium (Mg), and copper (Cu) can enhance secondary metabolite production, supporting plant defense mechanisms. This study evaluated the effects of P, Mg, and Cu fertilization on nutrient absorption and the production of phenolic and flavonoid metabolites in Pendok rice during vegetative and generative phases. A randomized block design with seven nutrient treatments and three replications was applied, involving 21 pots in a greenhouse. P was supplied as Super Phosphate Ca(H2PO4) (SP-36) and Phosphate Rock (PR). Mg and Cu treatments included combinations with and without their addition. Results showed that SP-36 with Mg produced the highest phenolic content during the vegetative phase, significantly higher than other treatments with 7.80 mg (GAE).g extract-1. Mg increased phenolic levels, while Mg and P had a significant effect (95% confidence level) on flavonoid and phenolic content during both growth phases. In conclusion, Mg and P fertilization effectively enhanced secondary metabolite production, improving plant resilience through nutrient optimization. These findings emphasize the role of proper nutrient management in boosting secondary metabolite quality in rice cultivation.